Peranan Pengurus dalam Pengembangan Yayasan Manggala Widya Sastra di Desa Batubulan Kabupaten Gianyar - Ni Putu Dea Oktaviani Dewi; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2022)
Foundation is an entity in the form of a law which is generally used in matters, especially in the field of education. The purpose of establishing the Foundation in the field of Education is to advance and educate the nation's generation. One of the foundations in Gianyar in the field of education is the Manggala Widya Sastra Foundation. This study aims to determine the position and function of the management in developing the Manggala Widya Sastra Foundation in Batubulan Village, Gianyar Regency and to determine the efforts made by the management in developing the Manggala Widya Sastra Foundation in Batubulan Village, Gianyar Regency. The research method uses empirical legal methods, with a conceptual approach. Data were obtained directly in the field, by observing and interviewing, which were then analyzed qualitatively and descriptively. The results showed that the foundation was formed with the consideration that in practice the development of an educational foundation in Indonesia is based on the interests of the community and their habits. The function of the board is to carry out the vision and mission of the foundation, to develop school facilities and to plan the school's annual budget in which the foundation also assists in managing administration and finances.